Consumer purchase intention towards store brands in Penang - Foong, Yinn Mean (2018)
Emerging store brands in the market is one of opportunities given to the marketers in marketing their products. Store brands provide more choices and alternative to consumers at a cheaper price compared to national brands. However, store brands in Malaysia are still experiencing a low market share. The main purpose of this study was to identify factors that influencing consumers’ purchase intention towards store brands in Penang. 391 respondents had participated in the study, they were chosen by using convenience sampling method. Data was collected through conducting questionnaire survey. Descriptive analysis was used to understand consumers’ demographic profile and their familiarity towards store brands. The demographic profile measured included gender, age, race, marital status, educational level, occupation, number of household members and personal income per month. Furthermore, in order to understand the pattern of consumers’ response towards the variables, median was generated. Ordinal regression analysis was carried out to determine the relationship between factors influence consumers purchase intention towards store brands and determine the factor which has the greatest impact on consumer purchase intention towards store brands. Finding shows that majority of the respondents understand the existence of store brand but they seldom purchase it. The result also showed that perceived value, perceived quality and subjective norm were the factors that will influence consumers’ purchase intention towards store brand. Among three of these factor, perceived value was the most significant factor that will influence consumers’ purchase intention towards store brands. Therefore, marketers should further invest in creating value for consumers because most of the consumers are value sensitive. With reasonable money spent, they can get big value, this is what consumers looking for.